Detailed micro-modelling of the direct shear tests of brick masonry specimens: The role of dilatancy. (1st August 2018) - Andreotti, G.; Graziotti, F.; Magenes, G.
Highlights: Interpretation of the different results from triplet tests and in situ shove tests. Influence of the expansion of masonry (ie dilatancy phenomenon) on the shear strength of bed joints. Micro-modelling capable to simulate the expansion of masonry during shear failure. Calibration of the parameters for the dilatancy of masonry with experimental data. Abstract: The mechanical parameters (shear strength of bed joints) derived from triplet tests can apparently be significantly different from those obtained through the so called "shove test" procedure executed on the same type of masonry. It was observed that this discrepancy may be caused by a wrong estimation of the compressive stress in the bed joints of the shove test. This article describes a numerical technique implemented in Abaqus to provide a sound interpretation of the phenomena involved in the failure of a mortar bed joint. The level of accuracy required to accomplish the objectives of the present study has driven the attention toward the detailed micro-modelling approach. Units and mortar joints have been modelled with continuum elements whereas the cohesive interfaces with zero thickness have been used for the unit-mortar interfaces. The material nonlinearities of masonry have been attributed to mortar and unit-mortar interfaces. The dilatancy of the bed joint during the shear failure process can generate, under certain boundary conditions, a local increase of the normal compression stress. Hence, particular attention has been dedicated to the modelling of this phenomenon. Several triplet tests and shove tests have been used as experimental benchmark for the numerical simulations. With the aim to accurately calibrate the parameter that controls the dilatancy, this work has paid attention also to the numerical-experimental comparison in terms of normal expansion of the joints, whereas commonly the comparison is generally carried out only in terms of shear stress-displacement curve. With the proposed technique, the triplet test and the shove test can be simulated with great accuracy. Thanks to these features, it has been also possible to relate the two types of test by highlighting the factors that affect the local normal stress during the shear failure process, providing a more detailed explanation of why and how the shove test results must be carefully interpreted in order to derive a realistic estimate of the shear strength of bed joints.